Infliximab Therapy Leading to Pulmonary Tuberculosis in a Patient With Negative Interferon γ Release Assay (IGRA)-Based QuantiFERON Gold Test. (July 2017) - Parita, Soni; Vivek, Kumar; Stephan, Kamholz; William, Pascal; Yizhak, Kupfer
Infliximab therapy is associated with higher rates of active tuberculosis (TB), particularly extrapulmonary and disseminated forms with unusual symptoms. We report the case of a 66-year-old man with Crohn's disease who developed TB mimicking lung cancer on imaging. He presented with cough and fever of 2 weeks' duration shortly after starting infliximab. Computed tomography of the chest revealed a 7.0 × 3.2 cm 2 pleural-based mass, highly suspicious for malignancy. Histopathological examination confirmed the diagnosis of TB. The mass disappeared after antitubercular treatment, and the patient recovered completely. A review of the literature suggests that TB masquerades as lung cancer clinically and radiologically. The classical lesions of TB are cavitatory with calcifications. Mass lesions without cavity or calcifications are rare and are mostly reported from regions endemic for TB. The majority of patients on infliximab therapy required biopsy for accurate diagnosis of TB because of its unusual presentation.